PARADOKS DIGITALISASI ADMINISTRASI PENDIDIKAN PADA GURU SEKOLAH MENENGAH PERTAMA - Ansori Zaini (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Digital transformation within the education system is expected to improve administrative efficiency and the quality of learning; however, in practice, it has instead given rise to new dynamics regarding teachers’ workloads. This study aims to analyse the impact of the digitalisation of educational administration on teachers’ professionalism using the Pedagogical Content Knowledge perspective. This study employs a descriptive qualitative approach and is based at SMP Negeri 1 Kanor, Bojonegoro Regency. Data were collected through in-depth interviews with research subjects selected through purposive sampling, involving teachers with diverse age and experience backgrounds. The results indicate that the digitalisation of administration increases teachers’ workload, primarily due to a lack of digital literacy and training, as well as the complexity of digital reporting systems. High administrative burdens result in teachers having reduced focus on instructional development. Furthermore, competence-building activities through online training tend to be merely a formality and have not yet contributed optimally to supporting pedagogical practice. This situation gives rise to an imbalance in mental workload, characterised by an overload in fulfilling administrative tasks and a decline in pedagogical activities within the classroom. Furthermore, competency development activities through online training tend to be formal and have not optimally contributed to supporting pedagogical practice. This condition gives rise to an unbalanced mental workload, namely an overload on fulfilling administrative tasks and a decrease in pedagogical activities in the classroom. Therefore, a restructuring of the teacher work system is needed to reduce the administrative burden, strengthen activities that support the development of Pedagogical Content Knowledge, and design proportional training and competency development. ABSTRAK Transformasi digital dalam sistem pendidikan diharapkan mampu meningkatkan efisiensi administrasi dan kualitas pembelajaran, namun dalam praktiknya justru menimbulkan dinamika baru terkait beban kerja guru. Penelitian ini bertujuan untuk menganalisis dampak digitalisasi administrasi pendidikan terhadap profesionalisme guru dengan menggunakan perspektif Pedagogical Content Knowledge. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan lokasi di SMP Negeri 1 Kanor, Kabupaten Bojonegoro. Data dikumpulkan melalui wawancara mendalam dengan subjek penelitian ditentukan secara purposive, melibatkan guru dengan latar belakang usia dan pengalaman yang beragam. Hasil penelitian menunjukkan bahwa digitalisasi administrasi meningkatkan beban kerja guru, terutama disebabkan minimnya literasi digital dan pelatihan, serta kompleksitas sistem pelaporan digital. Beban administratif yang tinggi berdampak pada berkurangnya fokus guru terhadap pengembangan pembelajaran. Selain itu, kegiatan pengembangan kompetensi melalui pelatihan daring cenderung bersifat formalitas dan belum berkontribusi optimal dalam mendukung praktik pedagogis. Kondisi ini memunculkan fenomena mental workload yang tidak seimbang, yaitu overload pada pemenuhan tugas administrasi dan menurunnya pada aktivitas pedagogis pembelajaran di kelas. Oleh karena itu, diperlukan penataan kebijakan yang lebih proporsional melalui pengurangan beban administratif, penguatan pelatihan, serta pengembangan model pembelajaran campuran guna mendukung optimalisasi kualitas pembelajaran.